2021
DOI: 10.2147/jpr.s287571
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment of Migraine with Celecoxib Oral Solution: Results of a Randomized, Placebo-Controlled Clinical Trial

Abstract: Background Nonsteroidal anti-inflammatory drugs are widely used for migraine, but gastrointestinal tolerability limits use. We previously reported results from the first treatment period of this 2-period, randomized, controlled study comparing DFN-15—an oral, ready-made liquid solution of a selective cyclo-oxygenase-2 inhibitor celecoxib—with placebo for the acute treatment of a moderate-severe migraine attack. Herein, we report the effects of treatment for the second treatment period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Our study results contrasted to other recent clinical trials conducting in the United States, the United Kingdom, and Germany, of which, the most commonly reported MBS was photophobia (range: 50.6%-59.9%), followed by nausea (16.4%-31.5%) and phonophobia (13.4%-29.8%). [29][30][31][32][33][34][35][36][37][38][39][40][41][42] Of note, most participants in those trials were White (range: 74.0%-88.2%). 30,35 In addition, two large-scale observational studies in the United States also reported photophobia as the most common MBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study results contrasted to other recent clinical trials conducting in the United States, the United Kingdom, and Germany, of which, the most commonly reported MBS was photophobia (range: 50.6%-59.9%), followed by nausea (16.4%-31.5%) and phonophobia (13.4%-29.8%). [29][30][31][32][33][34][35][36][37][38][39][40][41][42] Of note, most participants in those trials were White (range: 74.0%-88.2%). 30,35 In addition, two large-scale observational studies in the United States also reported photophobia as the most common MBS.…”
Section: Discussionmentioning
confidence: 99%
“…The MBS was used as a co-primary endpoint with the aim to better align the study outcome, 25 reduce sample size requirements, and potentially harmonize randomized controlled trial designs with "real-world" treatment experiences. 27,28 To date, most of the recent clinical trials adopting MBS as a co-primary endpoint have been conducted in Europe and the United States, [29][30][31][32][33][34][35][36][37][38][39][40][41][42] except for one study in Japan. 43 These studies reported photophobia as the most common MBS, ranging from 50.6% to 59.9% in patients from Europe and the United States; however, the frequency was noticeably lower in Japan (37.4%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, celecoxib capsules are slow to provide pain relief, with a median T max of 2.5 hours. 30 Because rapid pain relief is an important treatment goal, 30 , 31 and due to GI issues with oral NSAIDs, 30 celecoxib capsules have not been approved for the acute treatment of migraine in the U.S. 32 …”
Section: Introductionmentioning
confidence: 99%
“…29 However, celecoxib capsules are slow to provide pain relief, with a median T max of 2.5 hours. 30 Because rapid pain relief is an important treatment goal, 30,31 and due to GI issues with oral NSAIDs, 30 celecoxib capsules have not been approved for the acute treatment of migraine in the U.S. 32 ELYXYB (celecoxib oral solution, 25 mg/mL, previously known as DFN-15) is a new liquid formulation of celecoxib, approved in May 2020 for the acute treatment of migraine with or without aura in adults. 33 It has a shorter demonstrated T max (median 0.7 hours) than available celecoxib capsule formulations, 30 and has been evaluated and found effective versus placebo in a prior phase 3 randomized, double-blind, placebo-controlled trial of patients with episodic migraine (N=622).…”
Section: Introductionmentioning
confidence: 99%